Sinan's autobiographies : five sixteenth-century texts - Sinan, Mimar, 1489 or 1490-1588 (Studies and sources in Islamic art and architecture ;, 2006)
The sixteenth century Ottoman architect Sinan is today universally recognized as the defining figure in the development of the classical Ottoman style. In addition to his vast oeuvre, he left five remarkable autobiographical accounts, the so-called "Adsiz Risale", the "Risaletu'l-Mi'mariyye", "Tuhfetu'l-Mi'marin", "Tezkiretu'l-Mi'mariyye" and "Tezkiretu'l-Bunyan" that provide details of his life and works. Based on information dictated by Sinan to his poet friend Mustafa Sa'i Celebi shortly before his death, they exist in multiple manuscript versions in libraries in Istanbul, Ankara, and Cairo. The present volume contains critical editions of all five texts, along with transcriptions, annotated translations, facsimiles of the most important variant versions, and an introductory essay that analyzes the various surviving manuscripts, reconstructs their histories, and establishes the relationships between them.